2011
DOI: 10.1007/s12663-010-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Odontogenic Keratocyst of the Mandible

Abstract: Odontogenic keratocyst (OKC) is a cyst of dental origin with an aggressive clinical behavior, having high recurrence rate. Multiple cysts are associated with bifid-rib basal cell nevus syndrome (Gorlin syndrome). We present a case of bilateral odontogenic keratocyst in a cleft lip patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…2C) 19 . The caseous material accumulates as the keratinized stratified squamous epithelium lining sloughs into the cyst lumen 20 . These lesions are notorious for recurrence due to the crypts they form in the involved bone, and they have been known to invade adjacent soft tissues and even the skull base 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2C) 19 . The caseous material accumulates as the keratinized stratified squamous epithelium lining sloughs into the cyst lumen 20 . These lesions are notorious for recurrence due to the crypts they form in the involved bone, and they have been known to invade adjacent soft tissues and even the skull base 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…19 The caseous material accumulates as the keratinized stratified squamous epithelium lining sloughs into the cyst lumen. 20 These lesions are notorious for recurrence due to the crypts they form in the involved bone, and they have been known to invade adjacent soft tissues and even the skull base. 21,22 A systematic review of OKC management demonstrated a 17% to 56% recurrence rate with enucleation alone, whereas the addition of Carnoy's solution or decompression before enucleation lowered the recurrence rate to 1% to 8.7%.…”
Section: Odontogenic Keratocystmentioning
confidence: 99%
“…They present as painless swellings. [ 6 ] OKCs are typically seen as a solitary, lucent, unilocular lesion with smooth corticated borders on orthopantomogram (OPG). Literature is scanty on MRI features and includes T1-hypointensity and T2-hyperintensity in keeping with cystic nature of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The odontogenic keratocyst (OK) is defined as a cyst of odontogenic origin characterized by its parakeratinized stratified squamous epithelial lining with nuclear hyperchromatism in its basal cells organized in a palisade [1]. OK was first described in 1876 and named by Phillipsen in 1956, who associated it with a tendency to recur [2,3]. In the third edition of the WHO classification of head and neck tumors, published in 2005, OK changed its designation from developmental cyst to benign odontogenic neoplasm, replacing its name with keratocystic odontogenic tumor, based mainly on its aggressive behavior, high recurrence, and mutations in the PTCH gene [4].…”
Section: Introductionmentioning
confidence: 99%